Commerce and service in the small town: case study on Olho d'Agua das Flores-Alagoas / Comércio e serviço na cidade pequena: estudo de caso sobre Olho d'Água das Flores-Alagoas - Joana Vitória Agra Santos; Lhawenne Santana Vieira; Nathália Shayane Ferreira Abreu; Samara Conceição Ferreira da Silva; Williany Amorim de Oliveira; Matteus Freitas de Oliveira (Universidade Estadual de Alagoas, 2020)
The city of Olho d'Água das Flores, located in the Alagoas backlands, as well as many cities in Brazil, is classified as a small town, and its population uses and needs the most varied services and trade offered in the city. Given this, this paper aimed to analyze the process of trade diversification in the city of Olho d'Água das Flores through the analysis of spatial fixes, in order to provide an opportunity to approach the understanding of another scale of analysis, where inequalities , processes and agents that contribute to the formation of singular and articulated spaces in global logics. For this, a series of data / information was collected through field observations, questionnaires regarding trade and its development and interviews, along with a literature review about the importance of small towns, commerce and local cities. From this, it was possible to obtain as graphical results related to the view of merchants and consumers about small towns and commerce in general. In addition, a checklist of banking data was also compared, food and communication services in the cities of Olho d'Água das Flores and Santana do Ipanema